Generation of bovine decellularized testicular bio-scaffolds as a 3D platform for testis bioengineering - Di Filippo, Francesca; Brevini, Tiziana A. L.; Pennarossa, Georgia; Gandolfi, Fulvio (Frontiers in Bioengineering and Biotechnology, 2025)
Accelerating the genetic selection to obtain animals more resilient to climate changes, and with a lower environmental impact, would greatly benefit by a substantial shortening of the generation interval. One way to achieve this goal is to generate male gametes directly from embryos. However, spermatogenesis is a complex biological process that, at present, can be partially reproduced in vitro only in the mouse. The development of reliable 3D in vitro models able to mimic the architecture and the physiological microenvironment of the testis, represents a possible strategy to facilitate ex vivo haploid male gamete generation in domestic species. Here we describe the creation of bovine testicular bio-scaffolds and their successful repopulation in vitro with bovine testicular cells. In particular, bovine testes are subjected to three different decellularization protocols. Cellular compartment removal and extracellular matrix preservation are evaluated. The generated bio-scaffolds are then repopulated with bovine testicular fibroblasts. The results obtained demonstrate that the decellularization protocol involving the use of 0.3% sodium dodecyl sulfate (SDS) for 12 h efficiently eliminates native cells, while preserving intact ECM composition and microstructure. Its subsequent repopulation with bovine fibroblasts demonstrates successful cell homing, colonization and growth, consistent with the scaffold ability to sustain cell adherence and proliferation. Overall, the generated 3D bio-scaffolds may constitute a suitable artificial niche for ex vivo culture of testicular cells and may represent a possible strategy to reproduce spermatogenesis in vitro.